ANALYSIS OF DEVELOPMENT AND PERFORMANCE OF COOPERATIVES PLANTATION PARTNERSHIPS (STUDY ON PLANTATION COOPERATIVE MANAGEMENT OF PRIMARY COOPERATIVE CREDIT PROGRAM FOR MEMBERS (KKPA) IN SEBERIDA DISTRICT, INDRAGIRI HULU REGENCY) - Suwaji Suwaji; Aris Triyono (JURNAL MANAJEMEN DAN BISNIS, 2020)
One of the efforts to optimize smallholder plantation development programs' achievement is through a synergistic pattern of plantation development between large companies and farmer communities. The plantation partnership program with the Primary Cooperative Credit for Members (KKPA) pattern is hoped that harmonious, mutually beneficial, and sustainable plantation development can be realized. This research was conducted to compare plantation partnership cooperatives' development and performance with the Primary Cooperative for Members (KKPA) scheme in Seberida District, Indragiri Hulu Regency, Riau Province. This study uses a quantitative descriptive approach; the data used are primary and secondary. Data collection methods are documentation and questionnaires. The development of cooperatives is analyzed using growth indicators in members and participation of cooperative members, development of cooperative management, and growth in capital and business volume. Cooperative performance is analyzed using the Balanced Scorecard approach. With this approach, it is expected to provide a complete picture of the performance of the KKPA Cooperative from various aspects, namely; Financial aspects, customers, internal business processes, and organizational growth and learning aspects. The results showed, although the number of members did not experience a significant increase, the participation of members, cooperative management, and the growth of capital and business volume of the KKPA cooperative periodically showed the progress that was getting better. The performance of the Balanced Scorecard in the financial aspect can show a reasonably good performance. Performance on the customer aspect, internal business process, and growth and learning aspects of the KKPA Cooperative show adequate or moderate performance. These results also explain that in the financial and non-financial aspects, the KKPA Cooperative performance is still not optimal. The KKPA Cooperative still has to strive to improve its performance by planning. Furthermore, better financial governance, making business steps and strategies that are more value-added oriented and broadening the KKPA Cooperative vision that has far-reaching capabilities in the future.